National survey on the use of chemicals in the working environment: estimated exposure events. Issue 7 (July 1995) - Brandorff, N P; Flyvholm, M A; Beck, I D; Skov, T; Bach, E
Abstract : OBJECTIVES–To obtain knowledge about the use and distribution of hazardous chemicals in Danish industry. This knowledge is used to regulate the occupational environment and prevent hazardous exposure. METHODS–A national survey on the use of chemicals was carried out in 1989 in a stratified sample of 1448 Danish businesses. 13, 000 different chemical products were reported. Information on components in the chemical products was obtained from the Danish product register data base (PROBAS) and by inquiries to suppliers and manufacturers. At the end of the study the composition of about 9400 of the products was known. A model was developed to estimate national numbers of chemical exposure events as a supplement to data on weights of chemicals used. RESULTS–Data are presented for 36 chemical substances with chronic toxic effects and high estimated national numbers of exposure events for the industry groups included in the survey. Seven of the 36 substances are carcinogens, 17 are reproductive toxicants, 12 are allergens, and 18 are neurotoxicants according to listings of chronic toxicants used by the Danish authorities. The largest national number of exposure events was estimated for the industry groups manufacture of fabricated metal products, and personal services, cleaning, and hair dressing. These should have special attention in further preventive work. CONCLUSIONS–This survey on the use of chemicals is the first nationwide investigation in Denmark to delineate the use of all chemicals. The data have been used in a project to review occupational hazards in general in Danish industry. In the future, the data may be used as a basis for measuring chemical substitution, developing chemical safety, and as reference for more specific investigations and for follow up studies. Also job exposure matrices based on actual use of chemical products can be constructed.